Role of Endoscopy in Managing Complications Associated with Pancreaticoduodenectomy: Concise Review of Literature - Puri, Rahul; Mahajan, Akhil; Sundaram, Sridhar (Journal of Digestive Endoscopy, 2024)
Pancreaticoduodenectomy (PD) is a complex surgery for the management of periampullary tumors. It is associated with significant morbidity and mortality of 20% and 3 to 5% respectively. While early complications like delayed gastric emptying, hemorrhage, and collections are common, late complications like biliary and pancreatic anastomotic stenosis are also known to occur. With the increase in cases of pancreatic and periampullary cancers, there is an upward trend seen even in the rates of surgery. Endoscopy has emerged over the years as a tool for both evaluation and management of various complications. In this narrative review, we aim to provide a primer for gastroenterologists who are likely to be called upon for endoscopic management of post-PD complications.
Keywords: complications; endoscopy; pancreaticoduodenectomy